Introduksi Teknologi Budidaya Rumput Laut Sargassum sp. Untuk Produksi Bioethanol - Sukartono; Cokrowati, Nunik; Asri, Yuliana; Lumbessy, Salnida Yuniarti; Affandi, Rangga Idris; Muahiddah, Nuri; Marzuki, Muhammad; Rahmadani, Thoy Batun Citra; Anggraini, Irika Devi; Marno, Septhian (Universitas Mataram, 2024)
Abstract: Sargassum sp. seaweed is included in the category of brown macro algae that has not been cultivated and has not been optimally utilized. Sargassum sp. has economic value because it contains alginate and iodine which are utilized in the food, pharmaceutical, cosmetic, and textile industries. Sargassum sp. has a high carbohydrate content that can be converted into bioethanol and bioenergy. So that this potential can be developed to improve the community's economy and increase efforts to protect the environment from pollution from the use of fossil fuels. Sargassum sp. seaweed can be found in the waters of Gerupuk, Sengkol Village, Pujut District. Gerupuk is a hamlet that is included in the Mandalika Creative Economic Zone, among the community's livelihood activities is seaweed cultivation. Seaweed farmers in Gerupuk only cultivate K. alvarezii seaweed. They only know Sargassum sp. as a seaweed that grows wild and has no economic value. Sargassum sp. in Gerupuk is not utilized, so it needs to be educated on its benefits and utilization. This community service activity will be carried out in Gerupuk Hamlet, Sengkol Village, Pujut District, Central Lombok Regency. The output targets of this community service activity are appropriate technology for the cultivation of Sargassum sp. for bioethanol production, publications at national community service seminars and articles published in national community service journals indexed by sinta. The stages of implementing this activity are coordination of activities, counseling, demonstration of Sargassum sp. seaweed cultivation, mentoring, evaluation of activities, and collaboration with the Lombok Marine Aquaculture Center (BPBL). The expected results of this activity are that seaweed farmers in Gerupuk can cultivate Sargassum sp. to improve the household economy and the community economy. Keywords: Seaweed, Sargassum sp., cultivation, bioenergy, bioethanol.